Retrieval of Ice Samples Using the Ice Drone - Carlson, Daniel F.; Pasma, Jonathan; Jacobsen, Mathias Edslev; Hansen, Mads Holm; Thomsen, Steffen; Lillethorup, Jeppe Pinholt; Tirsgaard, Frederik Sebastian; Flytkjær, Adam; Melvad, Claus; Laufer, Katja; Lund-Hansen, Lars Chresten; Meire, Lorenz; et al. (Frontiers in Earth Science, 2019)
The ecological impacts of meltwater produced by icebergs and sea ice in the waters around Greenland are poorly understood, due in part to limited observations. Current field sampling methods are resource and labor-intensive, and not without significant risk. We developed a small, unmanned, and robotic platform to retrieve ice samples, while simultaneously eliminating risks to scientists and their support infrastructure. The IceDrone consists of a commercial hexcopter that is modified to retrieve shallow ice cores. We describe the design requirements, construction, and testing of the IceDrone. IceDrone’s capabilities were validated in the laboratory and during a field test in January 2019 near Nuuk (southwest Greenland). IceDrone retrieved shallow ice cores in hard and dry ice in harsh winter conditions. The field test led to modifications in the drilling head design and drilling process that enable it to retrieve samples in thin sea ice. All design files and software are provided in an attempt to rapidly enhance our collective understanding of ice-ocean interactions while improving the safety and productivity of field sampling campaigns.